Manipulating antecedent conditions to alter the stimulus control of problem behavior. - Kennedy, C H (1994)
In a three-phase study, antecedent conditions involving instructor's task demands and social comments were evaluated for 3 students with severe disabilities who emitted problem behavior. The results of a descriptive analysis (Phase 1) demonstrated that task demands served as antecedents for problem behavior, and social comments were generally associated with increased levels of positive social affect. In a subsequent experimental analysis (Phase 2), an instructor emitted high rates of social comments and gradually faded in task demands across sessions. The results of Phase 2 showed initial reductions in problem behavior to near-zero levels from the onset of intervention, with the successful reintroduction of task demands for all students. Phase 3 replicated the procedures of Phase 1. The results demonstrated that for 2 students, task demands no longer served as antecedents to problem behavior. The outcomes from two social validity assessments indicated that substantial improvements were perceived in student behavior and that the independent variable was a socially acceptable means of reducing problem behavior.